Determinants of Foreign Investment of U.S. Advertising Agencies - Terpstra, Vern; Yu, Chwo-Ming (Journal of International Business Studies, 1988)
This paper investigates the impact of several factors on the foreign investment of U.S. advertising agencies by using the theories on the determinants of foreign direct investment by manufacturing firms. For the two years examined, the hypotheses about the impact of host country market size, host country geographic proximity, firm size, firm's international operations experience, oligopolistic reaction, and presence of home country customers abroad are all confirmed. This paper also investigates the impact of oligopolistic reaction among the top ten and the second ten largest agencies and finds a stronger impact for the former.